COMPARATIVE EFFICACY OF FUNGICIDES AND BIOLOGICAL CONTROL AGENTS FOR THE MANAGEMENT OF CHICKPEA WILT CAUSED BY FUSARIUM OXYSPORUM F. SP. CICERIS - Y. Mahmood1; M. A. Khan; N. Javed; M. J. Arif (Journal of Animal and Plant Sciences, 2015)
Efficacy of fungicides and biological control agents were tested side by side both in vitro and in glass house against chickpea wilt pathogen. In-vitro study showed that Carbendazim was proved to be best by checking the mycelia growth with mean of 83.7 % growth inhibition over control. Almost similar result was obtained in Glass house assay where Carbendazim was proved to be best followed by all other fungicides at different concentrations. In dual culture test of bio control agents with Foc showed that Pseudomonas fluorescens had more mycelial growth inhibition of pathogen (Foc) with 70.94 % inhibition over control. Trichoderma harzianum was proved to be second best followed by Rhizobia spp. and Bacillus subtilis with 63.95%, 60.79% and 57.68% growth inhibition respectively. In glass house assay Pseudomonas fluorescens was proved to be most effective on one moderately resistant variety (Noor 91) and two susceptible varieties (Pb2000 and ICC131-21) showed highly disease reduction percentage with mean 76.78 over un-inoculated control. Comparative study of biological control agents and fungicides showed that both are almost equally effective against chickpea wilt disease. Seed treatment with Trichoderma harzanium followed by Carbendazim drenching was proved most effective by increasing the disease reduction percentage up to 93.75%.
Keywords: Chickpea; Carbendazim; Fusarium oxysporum f. sp. ciceris; Trichoderma harzianum; mycelial growth